Creating the initial vocational qualification from the German Microcensus : [paper presented at the RC33 Eighth International Conference on Social Science Methodology, 10 July 2012, University of Sydney] - Maier, Tobias [Verfasser]; Helmrich, Robert [Verfasser] (My University, 2012)
"After secondary education, school leavers generally specialize to compete on the labor market. This specific knowledge can be obtained through apprenticeship (vocational education and training) or higher education. This initial vocational qualification or trained occupation is supposed to have a high impact on further career paths of individuals in countries with a high degree of formalization in the education and training system, like Germany. However, in the German case, it is hard to find large data sources that measure the initial vocational qualification for all qualification levels (ISCED 3b-6) in conjunction with other socio-demographic variables." The German Labour Force Survey (LFS), an integral part of the German Microcensus, represents the official statistic on the population and the labour market in Germany and covers 1% of all households in Germany. Its purpose is to supply information on the economic and social position of the population, employment activity, the labour market and training. However, the inital vocational qualification of the the economically active population is not provided directly in the sample. But since the survey year 2005 every respondent is compulsory asked to specify the major field of study. By using this additional information the BIBB is able to reconstruct the 'initial vocational qualification' for everybody with a qualification equal and higher to ISCED 3b. This paper demonstrates the method of creating the initial vocational qualification and illustrates the idea behind clustering occupations according to their main focus of activity. It also shows how this method could be used for other countries carrying out the LFS." (Autorenreferat, BIBB-Doku)
Keywords: G 1.2.3 Qualifikationsentwicklungen; G 1.1.3 Mikrozensus; Berufsausbildung; Qualifikationsniveau; Berufsbildungsstatistik; Mikrozensus